ISOLATION, IDENTIFICATION AND BIOACTIVITY TEST OF NON POLAR COMPOUNDS ON n-HEXANE EXTRACT OF Haliclona (Reniera) fascigera FROM SAMALONA ISLAND-SPERMONDE ARCHIPELAGO - Hafiludin Uli; Alfian Noor; Fredryk Welliam Mandey; Ajuk Sapar (Marina Chimica Acta, 2016)
Isolation, identification and bioactivity test of nonpolar compunds has been conducted on n-hexane extract sponge Haliclona (Reniera) fascigera of the island Samalona, Makassar, South Sulawesi. Isolation techniques consist of maceration, partition, fractionation using 2 steps using vacuum column chromatography and flash column chromatography and also purification step. Identification of isolate was analyzed with TLC, FTIR, GC-MS, and 1H NMR. The research result was obtained isolate as much as 4 mg and clear solid form. FTIR analysis indicate functional group OH, CH2, CH3, C=O, =CH and C-O. Identification of spot TLC under UV light and spotting solvent show that the spot was active on UV long and short waves and dark brown with cerium sulphate. The results show that isolate A contain aliphatic and alcohol compounds. Bioactivity test results indicate that these isolate A be able to inhibit the growth of bacteria Staphylococus aureus with inhibition zone diameter were 11.60 mm (100 ppm); 10.40 mm (50 ppm); 9.50 mm (25 ppm); 6.50 mm (10 ppm); 6,60 mm (negative control); 17.40 mm (positive control) and against bacteria Escherichia coli with inhibition zone diameter were 6.70 mm (100 ppm); 6,10 mm (50 ppm); 5,90 mm (25 ppm); 5.85 mm (10 ppm); 5,20 mm (negative control); 18.60 mm (positive control).